Trimester-specific reference intervals for hemoglobin A1c in non-diabetic pregnancy in a Chinese population - Yuguo Deng; Danling Cheng; Guilian Liao; Xiaoyu Tan; Jinying Yang (BMC Pregnancy and Childbirth, 2023)
Abstract Background Physiological glycated hemoglobin (HbA1c) values in each trimester are not well defined. This study aimed to determine trimester-specific reference intervals for HbA1c levels in non-diabetic pregnant women in China. Methods In this cross-sectional study, 5,042 Chinese pregnant women from 6 to 41 weeks of gestation were screened. An inclusion of 4,134 non-diabetic women was made to determine the reference intervals, they were divided into three trimesters: trimester 1 (T1), 6 weeks to 13 weeks + 6 days, trimester 2 (T2), 14 weeks to 27 weeks + 6 days, and trimester 3 (T3), 28 weeks to 41 weeks + 6 days. A total of 4,134 women (T1 n = 760, T2 n = 1,953, and T3 n = 1,421) provided blood samples which were analyzed for HbA1c concentrations. HbA1c was measured using high-performance liquid chromatography. The median and percentile (2.5th to 97.5th) for the HbA1c reference intervals were calculated for each trimester. Results In total, 8,732 HbA1c measurements were taken. Reference intervals for HbA1c expressed as median and percentile (2.5th to 97.5th) for each trimester were: T1: 4.7 (4.0–5.5%), T2: 4.5 (3.9–5.3%), and T3: 4.8 (4.1–5.7%) respectively. The HbA1c levels were significantly lower in the second trimester compared to those in the first trimester (p < 0.0001), and higher in the third trimester compared to the second trimester (p < 0.0001). Conclusions The reference intervals for HbA1c levels were 3.9–5.7% with upper limits of 5.5% in the first trimester, 5.3% in the second trimester, and 5.7% in the third trimester. These findings highlight the importance of considering trimester-specific reference intervals for HbA1c in non-diabetic pregnant women to promote maternal and fetal health.